Four‐level robust model for a virtual power plant in energy and reserve markets. Issue 11 (16th April 2019) - Zhou, Yizhou; Wei, Zhinong; Sun, Guoqiang; Cheung, Kwok W.; Zang, Haixiang; Chen, Sheng
Abstract : The integration of distributed energy resources into a virtual power plant (VPP) can realise the scale merit. This study presents a novel approach for determining the optimal offering strategy of a VPP participating in the day‐ahead (DA), the spinning reserve (SR), and the real‐time (RT) markets. To hedge against multi‐stage uncertainties, the authors propose a robust mixed integer linear programming optimisation model that comprises four levels: (i) the optimal DA energy and reserve dispatch; (ii) the worst‐case realisation of uncertainties involved in DA market energy prices, SR market capacity prices, stochastic power production, and called balancing power; (iii) the optimal RT energy re‐dispatch; and (iv) the worst‐case realisation of uncertain RT market energy prices. Moreover, a tractable solution method based on strong duality theory and the column‐and‐constraint generation algorithm to solve the proposed four‐level formulation was developed. Finally, numerical results for a realistic case study demonstrate the efficiency and applicability of the proposed approach. The commercial benefits of this strategy are also evaluated.